Peliminary data on settlement and adaptation of the predator, cryptolaemus montrouzieri mulsant (Coleoptera: coccinellidae) in colonies of mealy bugs on citrus trees in the Syrian coast - Al-Khateeb, Nadia; Asslan, Louai (2009)
Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) is an efficient predatory species against the mealy bugs of Pseudococcidae and one of the most successful and common predators used, since 1892 when Koppel imported it from Australia and introduced it to California in the United States for controlling mealy bugs on citrus.
Includes reference.
1
Keywords: Beetles; Ladybugs; Citrus; Mealybugs; Colonies -- Syrian Coast